Executive Committee Agenda 2015-04-09 - Academic Senate:::::::::
Agenda approved. Chair Report. Minutes of 3/26/15 approved. Question for President. Question for Provost. CANDEL Discontinuance approved for Senate agenda. Statewide Senator Report. Vice Chair Report. Proposed Constitutional change to definition of faculty referred to Structure and Functions. Senate Reorganization proposals approved for Senate agenda. Senate agenda approved.